Tierra de Campos: Hispano-Celtic in the Western Duero Plateau (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
This paper studies a small group of toponyms, ethnonyms and hydronyms from the centre and northwest of the Duero plateau. The name of the river Valderaduey (medieval Aratoi) is related to the ethnonym Superatii transmitted by ancient literary sources and the different possible explanations are analysed, in relation, among other aspects, to the position of the accent in ancient Celtic. These names are studied, as well as that of the river Cea, the very name of the Vacceans, and the minor toponyms of the Bronze Plaque of Fuentes de Ropel, paying special attention to their geographical dispersion as a possible onomastic trace of a hypothetical Celtiberian or Hispano-Celtic movement from east to west, with the river valleys as milestones of the successive stages.
Keywords: Hispano-Celtic; Celtiberian; Toponymy; Ethnonymy; Western Duero Plateau; Position of the accent in Ancient Celtic